Perfluoroalkyl substances in the environment and biota from the coasts of the South China Sea: profiles, sources, and potential risks - Zhang, Jiaer; Xie, Yuxin; Zhang, Jingru; Ye, Mai; Diao, Jieyi; Wang, Jianwen; Sun, Qiongping; Wang, Tieyu (Frontiers in Environmental Science, 2024)
Perfluoroalkyl substances (PFAS) are an emerging class of contaminants that have been produced since the 1950s. The first report on PFAS to raise global concerns was published in 2001. Since then, many countries have implemented policies to control PFAS. In this study, PFAS in the water, sediment, and biota in coastal areas were surveyed to review their use since their earliest production by using chronological methods combined with previous policy restrictions imposed on PFAS. In the meantime, reports of existing PFAS were evaluated to assess the ecological and health risks of seafood consumption by coastal populations. Following the restrictions on PFAS, the concentrations of PFAS have been decreasing steadily. With regard to the current occurrences of PFAS in water and sediment, there is almost no ecological risk. However, different gender and age groups are still at risk of exposure to perfluorooctane sulfonate and require constant monitoring. It is expected that the negative impacts of PFAS on the environment and human health will continue to decrease with the implementation of the emerging pollution control policy by the Chinese government in 2023.